Enhancing non-communicable disease detection and education among elderly - Enny Fitriahadi; Fayakun Nur Rohmah; Asyhara Naela Arifin (Community Empowerment, 2024)
Non-Communicable Diseases (NCDs) often go undetected in their early stages due to a lack of evident symptoms or complaints. Among various NCDs, hypertension and diabetes mellitus are two of the most prevalent, closely linked to a range of health issues in older adults. To address this concern, this community service initiative aimed to conduct screening and provide education on NCDs as an initial step in early detection of health problems among the elderly. The implementation method involved health education and screenings, engaging midwives, village officials, and Aisyiyah health cadres. Screening results revealed that 71.43% of elderly individuals had hypertension, 34.39% were diagnosed with hyperglycemia, and 34.43% had blood sugar levels exceeding 200 mg/dl. Elderly individuals diagnosed with hypertension, diabetes mellitus, or at high risk for other NCDs were advised to seek further checkups and examinations at nearby healthcare facilities.